The case of left loin pain and aneurysm of the splenic artery - El-Reshaid, Kamel; Al-Bader, Shaikha; Markova, Zhaneta (Journal of Drug Delivery and Therapeutics, 2021)
True splenic artery aneurysms (SAA) are rare, but potentially fatal, lesions. They account for 60% to 70% of patients diagnosed with visceral artery aneurysms. They should be differentiated from pseudo ones since the etiology is different. They risk of rupture is high if diameter is > 2 cm and in child-bearing years. In this case report; we describe an encounter of SAA in a patient presenting with severe left loin pain and shock due to acute pyelonephritis. The aneurysm was 1.2 cm and was partially thrombosed and calcified indicating its stability and chronicity. The etiology, types and management of SAAs is discussed. Keywords: abdominal pain, aneurysm, pseudoaneurysm, rupture, splenic artery.